Qur’anic values and engineering studies: approaches and methods in the process of Islamizing engineering curriculum - Shuriye, Abdi Omar; Ismail, Ahmad Faris (Pearson Malaysia Sdn.Bhd, 2011)
Moral and religious awareness originate in human experience, and is cognized by reason as indispensable element of life for moral imperatives are the core of human survival and prosperity. Professional ethics should be studied in relation to and its role in enhancing and sustaining life experience in the world. Engineering values are virtual and universal as far as the general framework is concerned. On balance, both morality and akhlaq with minor semantical differences are symmetrical in nature. Our core concern is to relate Islamization to engineering or to attempt to Islamize engineering sciences providing an overview of Islamization of knowledge as a concept and relating it to engineering sciences and technologies. While Islamization of knowledge is a method to allure Muslims to return to the original ethos of Islam it is necessary that Muslims understand that the entire spectrum of knowledge including engineering have its origin in the Qur’an. The raison d'être of this work is to demonstrate a methodology for Islamizing engineering curriculum. In process we have select some courses taught in the faculty of engineering IIUM and suggested basic approaches of Islamizing it and in that we exhibited some techniques for Islamization. We would like to acknowledge the precious assistance and wholehearted cooperation bestowed to us by the Research Management Centre, International Islamic University Malaysia, during the course of this research. Without their technical and financial support this work would not be materialized.